Electronical educational and methodological complexes as a means of forming the professional competence of future doctors when studying disciplines from natural sciences - Batyuk, Liliya (Journal of Education, Health and Sport, 2015)
The article examines the possibilities of electronical educational and methodological complexes for the formation of professional competence of masters of higher medical education institutions and assessment of their academic achievements. It is claimed that obtaining a quality education is inextricably linked to the use of digital information and communication technologies, connected with the ability of students to understand electronic materials presented in the form of texts, graphs and tables, and to independently master theoretical material. Emphasis is placed on the tendency to use professionally oriented materials as a source of knowledge. The article presents the results of research into the forms and methods of effective implementation of electronical educational and methodical complexes on the Moodle platform among students which are studying at the Kharkiv National Medical University on the example of the academic discipline Medical and Biological Physics. The advantages and disadvantages of using electronic educational and methodological complexes in higher educational institutions are discussed.